BEHAVIORAL FINANCE AND GENDERED PATTERNS IN INVESTMENT CHOICES - Sugathan, Surabhi; Kumar, Amit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research explores behavioral finance to understand gendered investment choice patterns and focuses on how cognitive biases, emotional influences, and social factors shape financial decision-making. Thus, this study also examines several important data from various secondary sources such as women demonstrating a minimum of 72% higher participation in health insurance and 74% higher participation in life insurance than men. In contrast, fixed deposits are recurring at a rate of 54% for men and 49% for women to 46%. Using a mixed methods approach highlights disparities in investment choices and outcomes and provides a gender gap in financial decision-making in particular. In addition, the research, sustained with inductive methods and qualitative data, guides policymakers and financial institutions in developing gender-sensitive strategies that increase equitable investment opportunities and address biases in financial behaviors.